PAGSIPAT SA KAISIPAN NINA OROZCO AT DEMETERIO HINGGIL SA FERTILITY DANCE NG OBANDO, BULACAN GAMIT ANG KASAYSAYANG PASALITA (EXPLORING THE PERSPECTIVES OF OROZCO AND DEMETERIO ON THE OBANDO, BULACAN FERTILITY DANCE THROUGH ORAL HISTORY) - Delfin, Jennifer (Social Sciences and Development Review, 2025)
This study examined Orozco and Demeterio’s research work on the history of the Obando Fertility Dance. This research seeks to trace its origins through preliminary historical tracing from the perspective of the older Obandenyo, aged 60 to 90. The study attempts to answer the following questions: (1) What is the chronology of Obando’s patrons, as well as the actual ritual performed for San Pascual Baylon, Santa Clara, and the Blessed Virgin of Salambao? (2) How do the images and rituals associated with the celebration in Obando, Bulacan, transform each May? (3) What is the historical context and form of the ritual dance in Obando, Bulacan? It was analyzed in this research that Orozco and Demeterio’s thoughts coincide with oral histories shared by eight older Obandenyos. The Obando fertility dance may not be a product of Christianity, nor it was a version of a ritual by the Tagalogs even before the arrival of the Spanish. This may have started when the Spaniards arrived and when the patrons arrived. The majority of participants are unable to recall the term “Kasilonawan,” which could be the origin of the fertility dance that has just become Christianized.